Mechanisms involved in the biocontrol of rice sheath blight byWaitea circinata - Kellen Cristhina Inácio Sousa; Amanda Abdallah Chaibub; Jacqueline Campos Borba de Carvalho; Marta Cristina Corsi de Filippi; Leila Garcês de Araújo (Pesquisa Agropecuária Tropical, 2022)
The BRS Tropical rice cultivar was developed for tropical floodplains, but is susceptible to sheath blight, making the Waitea circinata bioagent an important tool in managing the disease. This study aimed to assess the W. circinata mechanisms involved in the parasitism and resistance induction to sheath blight. The in vitro antagonism was assessed by optical microscopy and scanning electron microscopy, followed by quantification of the lytic enzymes involved in parasitism, such as chitinase, glucanase and protease. An effect of the W.circinata mycoparasite against Rhizoctoniasolani was observed. The W. circinata application suppressed the sheath blight by up to 65 % and increased the chitinase, glucanase and lipoxygenase activity 72 h after the inoculation and that of the peroxidase 96 h after the inoculation. Thus, W. circinata showed to be efficient in suppressing sheath blight by parasitism and induced resistance via the activation of biochemical mechanisms.